Mechanistic study on the activity of manganese oxide catalysts for oxygen reduction reaction in an aprotic electrolyte. (10th March 2015) - Augustin, Matthias; Yezerska, Olga; Fenske, Daniela; Bardenhagen, Ingo; Westphal, Anne; Knipper, Martin; Plaggenborg, Thorsten; Kolny-Olesiak, Joanna; Parisi, Jürgen
Abstract: Despite a large effort in catalyst research over the past decade, the benefit of electrocatalysts for the oxygen evolution reaction (OER) and especially the oxygen reduction reaction (ORR) in the aprotic Li/air battery system has not yet been clarified. Here, three nanostructured manganese oxide catalysts – namely Mn3 O4, Mn5 O8 and α-Mn2 O3 – are investigated with regard to their activity for the ORR in a LiTFSI/DMSO electrolyte. In cyclic voltammetry (CV) measurements an overall decrease of potential gaps and an increase of re-oxidation efficiencies on carbon powder-based electrodes in comparison to glassy carbon (GC) was observed, which is attributed to the presence of more active centers, e.g. edges and kinks. Increased ORR potentials and the kinetic evaluation of the rate-determining step, namely the one-electron reduction of oxygen, point to a significantly enhanced activity of α-Mn2 O3 /C compared to pure carbon powder, Mn3 O4 /C and Mn5 O8 /C electrodes. This is discussed in terms of the electrocatalytic effect of α-Mn2 O3 for aprotic ORR processes. The ORR activity is proposed to originate from a different reaction pathway due to coordinatively unsaturated Mn 3+ ions on the surface of α-Mn2 O3, which act as active centers for associative adsorption and reduction of molecular O2 .